A Power-Law model of blood flow through a tapered artery with an overlapping stenosed - Ismail, Zuhaila; Abdullah, Ilyani; Mustapha, Norzieha; Amin, Norsarahaida (Elsevier Inc., 2008)
A mathematical model of non-Newtonian blood flow through a tapered stenotic artery is considered. The non-Newtonian model chosen is characterized by the generalized power-law model incorporating the effect of tapering due to the pulsatile nature of blood flow. The flow is assumed to be unsteady, laminar, two-dimensional and axisymmetric. The governing equations of motion in terms of the viscous shear stress in the cylindrical coordinate system are solved numerically using a finite difference scheme. Numerical results obtained for the positive taper angle show that the blood flow characteristics such as the axial velocity profiles, flow rate and wall shear stress have lower values, while the resistive impedances have higher values than the Newtonian model